2024
DOI: 10.1186/s12888-024-05571-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support and the severity of positive symptoms in rural community-dwelling patients with schizophrenia during the COVID-19 pandemic

Yudan Liu,
Hongying Liu,
Siyu Chen
et al.

Abstract: Background This study examined the association between social support and the severity of positive symptoms in rural community-dwelling schizophrenia patients during the COVID-19 pandemic. Method The cross-sectional study included 665 rural community-dwelling schizophrenia patients investigated during the COVID-19 pandemic. Social support was measured using the Social Support Rating Scale, and positive symptoms were assessed using the Positive Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Social Support Rating Scale (SSRS) is a self-rated instrument developed by Xiao Shuiyuan ( 20 , 21 ) and is one of the most widely used tools for assessing social support in China. Some studies have demonstrated good reliability and validity of this method in patients with severe mental illness in China ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Social Support Rating Scale (SSRS) is a self-rated instrument developed by Xiao Shuiyuan ( 20 , 21 ) and is one of the most widely used tools for assessing social support in China. Some studies have demonstrated good reliability and validity of this method in patients with severe mental illness in China ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Social Support Rating Scale (SSRS) is a self-rated instrument developed by Xiao Shuiyuan ( 20 , 21 ) and is one of the most widely used tools for assessing social support in China. Some studies have demonstrated good reliability and validity of this method in patients with severe mental illness in China ( 21 ). The SSRS is divided into three categories: subjective support, objective support, and support utilization, with a total score of 40, including items 1, 3, 4, 5 for subjective support, items 2, 6, 7 for objective support, and items 8, 9, 10 for support utilization across three dimensions.…”
Section: Methodsmentioning
confidence: 99%